Implementation of Social Studies Learning through Online: A Case Study at a Junior High School in Soreang Bandung - Lili Halimah; Idrus Affandi; Linda Nurkania; Yayuk Hidayah (STAI Hubbulwathan Duri, 2022)
This study aims to analyze the description of social studies learning through online, analyze the planning as well as the implementation of social studies learning, analyze evaluation of social studies learning through online at a junior high school in Soreang, Bandung Regency. The method used in the study uses a qualitative approach, the type of case study research. Data collection techniques in this study were observation, interviews and documentation. The result of the research is that online social studies learning is the result of a teacher council meeting at the direction of the Ministry of Education and Culture and the Bandung Regency Education Office. Social studies learning planning through online is prepared with reference to the 2013 Curriculum which is simplified and adapted to the needs of social studies subjects without being burdened with demands to complete all curriculum achievements and is focused on life skills education in the midst of the Covid-19 pandemic. The implementation of social studies learning through online is generally carried out with asynchronous learning (not interactive) with virtual classroom media from Google Docs and the like which are modified by the teacher according to the needs of social studies subjects. Evaluation of social studies learning through online is carried out in three ways, namely (1) knowledge through tests using Google Form media and assignments using Google Drive media; (2) skills through projects and portfolios with Google Drive media; (3) attitude through attendance and discipline to follow all learning activities by referring to the teacher's notes.